EXPLORATION OF POTENTIAL NATURAL COMPOUNDS THROUGH IN SILICO APPROACH: A CASE STUDY ON TOKARAMID COMPOUNDS - Baroroh, Umi; Sin, Cindy Wan Yik; Riasari, Hesti (Sekolah Tinggi Farmasi Indonesia, 2023)
Indonesia, renowned for its rich biodiversity, boasts diverse marine ecosystems that have long remained untapped in the quest for novel therapeutic compounds. This shows the great potential of Indonesia's biodiversity, particularly within its marine habitats, as a treasure trove for exploring bioactive compounds for disease treatment. These compounds can be explored using in silico analyses, including activity prediction, ADME (absorption, distribution, metabolism, and excretion) prediction, toxicity prediction, and molecular docking, to accelerate the discovery of promising drug candidates. The compound TG-0205221, modified Tokaramide A from the sponge Theonella mirabilis, is reported to have potential as an anti-3CLPro from SARS-CoV-1, which is genomically similar to SARS-CoV-2 by 96%. 3CLPro is the most prospective working target of anti-COVID-19. In this study, the exploration of TG-0205221 and Tokaramide A as anti-3CLPro was conducted using in silico approach. It is shown that based on ADMET prediction, all compounds are anticipated to be suitable for oral consumption and exhibit a non-toxic profile. TG-0205221 is predicted to have activity as a 3CLPro inhibitor higher than others. Furthermore, the potential anti-3CLPro SARS-CoV-2 activity of all ligands in molecular docking is envisaged to be considerably high. The binding energy of Tokaramide A and TG-0205221 is relatively similar, -9.16 and -8.39 kcal/mol, respectively. Both Tokaramide A and TG-0205221 show potential as anti-SARS-CoV-2 agents and may aid in the exploration of natural compounds for drug discovery.